HEMICHOREAHEMIBALISMUS DENGAN HIPERGLIKEMIA NONKETOTIK PADA STROKE ISKEMIK AKUT - Safridawati,* Hidayaturrahmi,*Natasya Wanda,* Nova Dian Lestari,* Syahrul* (NEURONA, 2020)
HCHB ASSOCIATED WITH NONKETOTIC HYPERGLYCEMIA IN ACUTE ISCHEMIC STROKE IS A WELLRECOGNIZED SYNDROME CHARACTERIZED BY THE SUDDEN OCCURRENCE OF HEMICHOREA OR MORE SEVERE EXPRESSION LIKE HEMIBALLISM THE HYPERKINETIC MOVEMENTS INVOLVE THE FACE ARM OR LEG HCHB IN ACUTE ISCHEMIC STROKE IS A MOVEMENT DISORDER THAT IS RARELY REPORTED WITH HYPERKINETIC MOVEMENT